Speak-up analytics: a voice activation system for data analytics / Mohammad Nasir Abdullah ... [et al.] - Abdullah, Mohammad Nasir; Mohamed Ariff, Mohamed Imran; Md Jelas, Imran; Arsad, Roslah (2022)
Speak-up analytics was developed by using R programming under R-Studio. This project proposed a simple interactive web base system to help users to do better performance in data analysis. This system allows any users to do data analytics without any hand gestures, but they just speak up and tell the machine to do the analytics. Some basic functions were developed in this system, such as sorting, arrange, filtering, grouping, counting and basic plotting. With Speak-up Analytics, the users only need to give instructions to the machine, and the machine will execute it to perform the analysis. For example, for arranging year descending, the machine will pick up the word, and arrange the year by descending order. The goal of this project is to manipulate the data using voice-activated commands. The list of commands used to instruct this system to manipulate tables dan data is sort, table remove, group by, filter and arrange. For plotting, this project has also successfully applied voice activation command to plot several graphs such as histogram and scatter diagram. This system will benefit non-analytic person to screen and handle data without prior knowledge in programming and query language.